The Doctrine of Equivalent Protection - Accessory Conventional Standard for Failure to comply with the European Arrest Warrant - Mirianashvili, George (Journal of Law, 2019)
This article reviews the doctrine of equivalent protection, process of its origin and development, sphere of effect and extradition quasi-effects of the spread over the European system. The doctrine of Equal Protection regardless of granting privileges to the European Union and its member states in the European Convention System, it is also conventional mechanism for non-compliance with the European arrest warrant. This, as an instrument enables extradition quasi-European Court of Human Rights shall consider a case in concreto for violation of the European Convention by fulfilling the obligations under the European system, on the one hand and shall impose a responsibility on the Member State of the Union, and the national court shall not enforce the European arrest warrant in accordance with the Convention's standards, on the other hand. Authorial test of non-compliance with the European arrest warrant is proposed in the article based under the doctrine of Equal protection.